Complete genome sequence of Treponema paraluiscuniculi, strain Cuniculi A: the loss of infectivity to humans is associated with genome decay - Šmajs, David; Zobaníková, Marie; Strouhal, Michal; Čejková, Darina; Dugan-Rocha, Shannon; Pospíšilová, Petra; Norris, Steven J; Albert, Tom; Qin, Xiang; Hallsworth-Pepin, Kym; Buhay, Christian; Muzny, Donna M; et al. (PloS one, 2011)
Treponema paraluiscuniculi is the causative agent of rabbit venereal spirochetosis. It is not infectious to humans, although its genome structure is very closely related to other pathogenic Treponema species including Treponema pallidum subspecies pallidum, the etiological agent of syphilis. In this study, the genome sequence of Treponema paraluiscuniculi, strain Cuniculi A, was determined by a combination of several high-throughput sequencing strategies. Whereas the overall size (1,133,390 bp), arrangement, and gene content of the Cuniculi A genome closely resembled those of the T. pallidum genome, the T. paraluiscuniculi genome contained a markedly higher number of pseudogenes and gene fragments (51). In addition to pseudogenes, 33 divergent genes were also found in the T. paraluiscuniculi genome. A set of 32 (out of 84) affected genes encoded proteins of known or predicted function in the Nichols genome. These proteins included virulence factors, gene regulators and components of DNA repair and recombination. The majority (52 or 61.9%) of the Cuniculi A pseudogenes and divergent genes were of unknown function. Our results indicate that T. paraluiscuniculi has evolved from a T. pallidum-like ancestor and adapted to a specialized host-associated niche (rabbits) during loss of infectivity to humans. The genes that are inactivated or altered in T. paraluiscuniculi are candidates for virulence factors important in the infectivity and pathogenesis of T. pallidum subspecies.
Keywords: Sequence Analysis, DNA; sekvenční analýza DNA; Molecular Sequence Data; molekulární sekvence - údaje; genom; Genome; lidé; Treponema; Humans